A comparative study between agonist and antagonist protocol for ovarian stimulation in art cycles at a rural set up in South Gujarat - Nadkarni, Purnima Kishor; Nadkarni, Kishore Mohan; Kalyani, Kanika Rajendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Modern infertility practice provides us with several protocols for controlled ovarian hyperstimulation for the ART (Assisted Reproductive Techniques) cycles. The review summarises the clinical characteristics of the protocols using Gonadotrophin Releasing Hormone (GnRH) agonists and antagonists emphasising on the major clinical and laboratory outcomes with each protocol. Methods: A total of 322 cases undergoing ovarian stimulation with agonist and antagonist protocols in ART cycles at a rural set up at Killa Pardi in the year 2014 were studied and their laboratory and clinical outcomes were evaluated. Results: Antagonist group had the maximum number of oocytes retrieved and the mature M2 oocytes, maximum No. of follicles >16 mm on day of HCG, maximum No. of positive pregnancy rates. Agonist group had also a good pregnancy rate with maximum Grade I embryos. Conclusions: Taking all data together, it may be concluded that antagonists and minimal ovarian stimulation with antagonist protocols offer a new treatment regimen in ovarian stimulation that is short, safe, cost effective, well tolerated, optimizing convenience for the patient.